Neutrophil‐to‐lymphocyte ratio is a predictor of early graft dysfunction following living donor liver transplantation. (8th April 2019) - Kwon, Hye‐Mee; Moon, Young‐Jin; Jung, Kyeo‐Woon; Park, Yong‐Seok; Jun, In‐Gu; Kim, Seon‐Ok; Song, Jun‐Gol; Hwang, Gyu‐Sam
Abstract: Background & Aims: Early allograft dysfunction (EAD) is predictive of poor graft and patient survival following living donor liver transplantation (LDLT). Considering the impact of the inflammatory response on graft injury extent following LDLT, we investigated the association between neutrophil‐to‐lymphocyte ratio (NLR) and EAD, 1‐year graft failure, and mortality following LDLT, and compared it to C‐reactive protein (CRP), procalcitonin, platelet‐to‐lymphocyte ratio and the Glasgow prognostic score. Methods: A total of 1960 consecutive adult LDLT recipients (1531/429 as development/validation cohort) were retrospectively evaluated. Cut‐offs were derived using the area under the receiver operating characteristic curve (AUROC), and multivariable regression and Cox proportional hazard analyses were performed. Results: The risk of EAD increased proportionally with increasing NLR, and the NLR AUROC was 0.73, similar to CRP and procalcitonin and higher than the rest. NLR ≥ 2.85 (best cut‐off) showed a significantly higher EAD occurrence (20.5% vs 5.8%, P < 0.001), higher 1‐year graft failure (8.2% vs 4.9%, log‐rank P = 0.009) and higher 1‐year mortality (7% vs 4.5%, log‐rank P = 0.039). NLR ≥ 2.85 was an independent predictor of EAD (odds ratio, 1.89 [1.26‐2.84], P = 0.002) after multivariable adjustment, whereas CRP and procalcitonin were not. Increasing NLR was independently associated with higher 1‐year graft failure and mortality (both P < 0.001). Consistent results in the validation cohort strengthened the prognostic value of NLR. Conclusions: Preoperative NLR ≥ 2.85 predicted higher risk of EAD, 1‐year graft failure and 1‐year mortality following LDLT, and NLR was superior to other parameters, suggesting that preoperative NLR may be a practical index for predicting graft function following LDLT.